36 Medication prescriptions in 322 functional motor disorder patients in a large UK mental health service: a case control study. (28th May 2019) - O'Connell, Nicola; Nicholson, Timothy; Blackman, Graham; Tavener, Jennifer; David, Anthony S
Abstract : Objectives: This study aims i) to describe the patterns of prescription medication in functional motor disorder (mFND) treated in a Mental Health Trust, using a control group comprised of a random sample of contemporaneous patients treated in the same trust; and ii) explore the sociodemographic variables and symptoms linked to higher medication usage. Methods: This is a retrospective case-control study using an electronic psychiatric case register in South London and Maudsley NHS Foundation Trust (SLaM). SLaM provides psychiatric inpatient and community services and receives national referrals for functional neurological disorder (FND) patients. Data were obtained from 322 mFND patients and 644 controls between 1 st January 2006 and 31 st December 2016 using the 'Clinical Records Interactive Search' (CRIS) database. Results: 247 (76.7%) mFND patients were prescribed medication, lower than 83.4% in the control group (OR: 0.59, 95% CI: 0.39–0.89, p<0.02). The mean number of prescribed medications in the mFND group was 4.77 (SD: 2.4), higher than 2.98 (SD: 2.7) in the psychiatric control group ( t (782)=7.9, p=0.001). Amongst mFND patients receiving medication, the most common prescriptions were antidepressants (68% received one or more), anti-epileptics (33.5% on one or more), non-opioid painkillers (32.4%), and opioid analgesics (31.2%). Compared to psychiatric controls, mFND patients had a higher likelihood of receiving anti-depressants, medications for cardiovascular disease, statins, antihistamines, anti-asthmatics, corticosteroids, anti-epileptics, hormone replacement therapy, proton pump inhibitors, bowel and urinary dysfunction medication, NSAIDs, and muscle relaxants. mFND patients were significantly less likely to receive antipsychotic medication or treatments for substance misuse. An adjusted analysis of mFND patients found co-morbid physical conditions and previous psychiatric admissions were associated with higher numbers of medication prescriptions. Conclusions: mFND patients are prescribed an extensive range of medications for psychiatric and somatic symptoms, most commonly anti-depressants, anti-epileptics and analgesics. The diversity in medications may be partially explained by higher rates of physical co- morbidities but may also reflect 'somatisation' or excessive symptom reporting combined with a lack of therapeutic options for clinicians managing patients with complex functional and 'organic' conditions and chronic pain. Non-essential medication prescribing may reinforce somatic illness beliefs and cause iatrogenic harm, particularly high rates of opioid pain medication, with important implications for clinical management in primary and secondary care.